PENEGAKAN HUKUM TERHADAP TINDAK PIDANA UJARAN KEBENCIAN MELALUI MEDIA SOSIAL DITINJAU DARI UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Andry, Andry; Soetoto, Erwin Owan Hermansyah; Atmoko, Dwi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Law enforcement against criminal acts of hate speech is still faced with various obstacles, both originating from material law and formal rules. The problems in this study are (1) How is law enforcement against criminal acts of hate speech through social media in terms of the Law of the Republic of Indonesia Number 19 of 2016 concerning Information and Electronic Transactions?, (2) What factors are involved? become an obstacle to the enforcement of criminal acts of hate speech through social media? The research method used is normative juridical, descriptive analytical research specifications. Based on the results of the research, in cases of criminal acts of hate speech it is hoped that there will be firmness in these crimes, so that there are no misunderstandings that ultimately harm the people. In an effort to enforce the law against hate speech crimes, the National Police bases its authority on the ITE Law as regulated in Article 27 paragraph (3) and Article 28 junto Article 45 paragraph (2).